2023
DOI: 10.1136/jitc-2022-005519
|View full text |Cite
|
Sign up to set email alerts
|

Engineering second-generation TCR-T cells by site-specific integration of TRAF-binding motifs into theCD247locus

Abstract: BackgroundThe incorporation of co-stimulatory signaling domains into second-generation chimeric antigen receptors (CARs) significantly enhances the proliferation and persistence of CAR-T cells in vivo, leading to successful clinical outcomes.MethodsTo achieve such functional enhancement in transgenic T-cell receptor-engineered T-cell (TCR-T) therapy, we designed a second-generation TCR-T cell in which CD3ζ genes modified to contain the intracellular domain (ICD) of the 4-1BB receptor were selectively inserted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
0
1
0
Order By: Relevance
“…Recent studies have reported that the insertion of 4-1BB into the TCR structure can enhance the activation signals within T cells, but the location of 4-1BB relative to the CD3ζ domain (N-terminal or C-terminal) significantly affects TCR formation. The fusion of the 4-1BB domain to the N-terminal of CD3ζ could fail to constitute the TCR complex 16 . As for CAR, the location preference for co-stimulatory signaling domain modification is reversed, reflecting another significant structural difference.…”
Section: Synthetic Receptors For Programing T Cellsmentioning
confidence: 99%
“…Recent studies have reported that the insertion of 4-1BB into the TCR structure can enhance the activation signals within T cells, but the location of 4-1BB relative to the CD3ζ domain (N-terminal or C-terminal) significantly affects TCR formation. The fusion of the 4-1BB domain to the N-terminal of CD3ζ could fail to constitute the TCR complex 16 . As for CAR, the location preference for co-stimulatory signaling domain modification is reversed, reflecting another significant structural difference.…”
Section: Synthetic Receptors For Programing T Cellsmentioning
confidence: 99%
“…TCR-T cells overexpressing c-Jun and targeting hepatocellular carcinoma could improve the survival of mice with tumor growth [124] . The fusion of the TRAF-binding motif from 4-1BB ICD at the C-terminal of CD3z could enhance the persistence and expansion of TCR-T cells both in vitro and in vivo [125] . The induced expression of IL-12 in the PDCD1 locus could enhance the function of NY-ESO-1-specific TCR-T cells and eliminate established tumors in a xenograft mouse model, with greater TCR-T cell expansion potential [126] .…”
Section: Strategies To Improve Tcr-t Cell Therapy Beyond Tcr Engineeringmentioning
confidence: 99%